First report on the population dynamics of Egeirotrioza ceardi (DeBergevin) (Hemiptera: Psyllidae) on Euphratica poplar trees in Iraq - Rabeea, A. A. (International Journal of Agricultural Technology, 2021)
Poplar Psyllids, Egeirotrioza ceardi (DeBergevin) (Hemiptera: Psyllidae) is an important pest of Euphratica poplar trees in Iraq. This study was included different leaf shapes of Populus euphratica (Olivier) as cordate, reniform, oval and ovate. The nymphs moved to the leaf surface of Populus euphratica and they were begun feeding by sucking the sap from leaf tissues. Leaf tissues were surrounded the nymph to form small opened causing leaf deformation. Noteworthy all stages of growth and development of E. ceardi were present on the upper surface of the examined leaves. Results indicate numerical density and monthly population density of the insect on poplar trees was fluctuated during this period and reached its highest level in June (102 and 667) nymph /leaf. The proportion of nymphs on the leaf surface was associated with a gradual increase on the reniform shape of the leaf. The activity period of nymphs may be affected by environmental condition especially temperature and relative humidity (RH). Among the different shapes of P. euphratica leaves had the highest infection that occurred when temperature and humidity are 35° and 19% respectively. This study will be helpful in knowing the assessment of incidence and severity of damage caused by the E. ceardi. So that, the proper control measures can be used in future to minimize the load of insecticides. It is firstly reported on the population dynamics of E, ceardi on Euphratica poplar trees in Iraq